PERLINDUNGAN HUKUM HAK DAN KEWAJIBAN DOSEN TERHADAP INTERVENSI YAYASAN PADA PERGURUAN TINGGI - PERMAI YUDI; KRISTA SURBAKTI (KULTURA DIGITAL MEDIA ( Research and Academic Publication Consulting ), 2020)
Law no. 14/2005 on Teachers and Lecturers and Government Regulation of the Republic of Indonesia No. 37/2009 on Lecturers certainly guarantees the existence of lecturers in universities both public and Private, especially swata universities often face off between lecturers and college managers namely foundations. The Foundation as one of the institutions that has a license to establish and or manage high-profile institutions often ignores the rules that apply in accordance with the laws and regulations, sometimes the foundation of a college often intervenes in the policies that will be issued by the head of the college, often harming the lecturers who are based in the college, thus harming the rights of lecturers, and not keeping agreements or contact work towards permanent lecturers or non-permanent lecturers. To ensure legal protection for lecturers both permanent and non-permanent in universities managed by the Foundation, therefore there needs to be more in-depth research on the Legal Protection of Lecturers' Rights and Obligations against Foundation Intervention in Universities This research is a normative empirical juridical research, namely by conducting an analysis of the problem through studying the legal norms contained in the laws and regulations in Indonesia and looking at the reality that occurs in the field. How is it technically done in the field against the rights and obligations of lecturers to the intervention of the foundation, whether in accordance with the applicable laws in Indonesia. In search of a good solution or solution, and the realization of a sense of fairness or not can be seen in the results of this study that will be published in the mandatory luran namely a national journal accredited or un accredited and will be publicly publicized on the additional outside of international journals. This research is financed by the Ministry of Research and Technology, Research Lecturer Beginner (PDP) in the year of implementation 2020, and researchers thank the parties who have been willing and helpful in the research, so that this research can be completed, although there are still many shortcomings or errors in both name typing, place and others.